2020
DOI: 10.4196/kjpp.2020.24.4.329
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin reduces fluid hypersecretion by inhibiting TMEM16A in interleukin-4 treated Calu-3 airway epithelial cells

Abstract: Rhinorrhea in allergic rhinitis (AR) is characterized by the secretion of electrolytes in the nasal discharge. The secretion of Cland HCO 3 is mainly regulated by cystic fibrosis transmembrane conductance regulator (CFTR) or via the calciumactivated Clchannel anoctamin-1 (ANO1) in nasal gland serous cells. Interleukin-4 (IL-4), which is crucial in the development of allergic inflammation, increases the expression and activity of ANO1 by stimulating histamine receptors. In this study, we investigated ANO1 as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…66,67 Although both anti-inflammatory and anti-oxidant activities do not always coexist in the same molecules, their coexistence is fortuitously common in bioflavonoids such as luteolin in particular. [68][69][70] These activities are intrinsically linked to the multitude of other bioactivities such as anti-allergenic actions 66 as demonstrated in a cell model of canine atopic dermatitis in which luteolin significantly inhibited the release of IL-33, IL-1β, IL-6, and IL-8 71 and in human allergic rhinitis, 72 which is probably mediated by IL-4 inhibition, which in turn suppresses the expression of the ANO1 calcium-activated Cl − channel, which is linked to nasal hypersecretion. Luteolin has also been shown to alleviate rheumatoid arthritis, a serious tumor necrosis factor-α (TNF-α) mediated autoimmune disease.…”
Section: Luteolin Modulation Of Systemic Inflammationmentioning
confidence: 99%
“…66,67 Although both anti-inflammatory and anti-oxidant activities do not always coexist in the same molecules, their coexistence is fortuitously common in bioflavonoids such as luteolin in particular. [68][69][70] These activities are intrinsically linked to the multitude of other bioactivities such as anti-allergenic actions 66 as demonstrated in a cell model of canine atopic dermatitis in which luteolin significantly inhibited the release of IL-33, IL-1β, IL-6, and IL-8 71 and in human allergic rhinitis, 72 which is probably mediated by IL-4 inhibition, which in turn suppresses the expression of the ANO1 calcium-activated Cl − channel, which is linked to nasal hypersecretion. Luteolin has also been shown to alleviate rheumatoid arthritis, a serious tumor necrosis factor-α (TNF-α) mediated autoimmune disease.…”
Section: Luteolin Modulation Of Systemic Inflammationmentioning
confidence: 99%
“…Furthermore, evidence from in vivo studies has revealed that other flavonoids, such as luteolin, myricetin, naringenin, baicalin, rosmarinic acid, procyanidins, and catechin, were also able to reduce nasal itching and sneezing frequency, infiltration of inflammatory cells, nasal mucosa thickness and mucus secretion as well as decrease the levels of allergenspecific IgE in murine models of allergic rhinitis [165,169,[246][247][248][249][250][251][252]. These findings support the potential therapeutic application of flavonoids in the treatment of allergic rhinitis; however, the clinical studies are limited.…”
Section: Allergic Rhinitismentioning
confidence: 99%
“…Furthermore, polyphenols need to be investigated in terms of routes of administration, target tissues, adequate doses, as well as the most appropriate composition of phenolic extracts, as it appears that a combination of polyphenols may lead to a more effective beneficial effect. The potential use of polyphenols as preventive and therapeutic interventions requires preclinical studies testing a wide range of doses to determine the maximum safe single dose and the long-term safety profile polyphenols, owning to their natural origin, are essentially considered to be non-toxic and safe, which is further supported by data from preclinical and clinical studies reporting good tolerability of the evaluated phenolic compounds with the advantages of no adverse effects and high safety [169,220,[244][245][246][247]249,[253][254][255]274,275,[282][283][284][285][286][287][288][289]293,294]. However, the amount of data available in this area is limited, and additional research is needed to assess the overall toxicity, and content of toxic substances generated during the polyphenol extraction process or food processing.…”
Section: Limitations and Future Challengesmentioning
confidence: 99%
“…The TMEM16A Ca 2+ -activated Cl À channel exerts diverse cellular functions in inflammatory diseases. For example, TMEM16A overexpression in airway and intestinal epithelial cells can result in excessive fluid secretion in inflammatory diseases such as allergic rhinitis [60,134,135] and infectious diarrhea [42][43][44]89]. In addition, increased TMEM16A expression level and activity in goblet cells contribute to goblet cell metastasis and mucus hypersecretion under inflammatory conditions [6,[60][61][62]65,66] and airway inflammatory diseases such as asthma [13].…”
Section: Cellular Environment-dependent Role Of Tmem16a In Inflammationmentioning
confidence: 99%